Carbon-embedded hierarchical and dual-anion C@MoSP heterostructure for efficient capacitive deionization of saline water. (10th August 2021) - Zhao, Meiqi; Zhao, Zhibo; Ma, Xiangdong; Zhao, Jingxuan; Ye, Meidan; Wen, Xiaoru
Highlights: Faradic deionization (FDI) with the outstanding desalination capacity and high feed salt concentration is emerging as a promising desalination technology. A carbon-embedded hierarchical and dual-anion C@MoSP heterostructure was synthesized by a facile hydrothermal method accompanied by the phosphorization treatment. The C@MoSP electrode realized an outstanding adsorption capacity of 25.43 mg/g, excellent adsorption rate, and good durability. The strong synergy of highly conductive carbon and dual anions boosted the CDI performance of pristine MoS2 . Abstract: Recently, two-dimensional transition-metal disulfides (TMDs) with amazing chemical and physical superiorities are emerging as promising faradic ion intercalation materials for effective capacitive deionization (CDI) application. Herein, a carbon-embedded hierarchical and dual-anion C@MoSP nanoflowers was synthesized by a facile hydrothermal reaction accompanied by the phosphorization treatment, and explored as an advanced CDI electrode material. Benefiting from the specific microstructure (e.g., hierarchically porous arrangement, enriched porosity and highly open pore network) and the strong synergistic effect of highly conductive carbon and low-electronegativity P dopant, the C@MoSP electrode demonstrated high surface area, enrich accessible interlayer, superior ion diffusion pathway and good electric conductivity for effective salty ion intercalation/deintercalation; Accordingly, the C@MoSP electrode realized an outstanding gravimetric adsorption capacity of 25.43 mg/g, excellent intercalation rate, and good durability in a NaCl aqueous solution with an initial concentration of 500 mg/L at an operation voltage of 1.2 V, which were evidently enhanced in comparison to MoSP and pristine MoS2 ones. Graphical abstract: Image, graphical abstract